Minimizing Cost of Milk Raw Material Inventory Using the Economic Order Quantity (EOQ) Method : Minimasi Biaya Persediaan Bahan Baku Susu Dengan Menggunakan Metode Economic Order Quantity (EOQ) - Priyanto, Anugerah Dany; Winursito, Yekti Condro; Nugraha, Isna; Sholeha, Fitriatus; Fanani, Handre Syahrul (Universitas Muhammadiyah Sidoarjo, 2023)
Inventory in raw materials is a very important thing to pay attention to by the company in carrying out its business processes. Economy Order Quantity (EOQ) is a method that is generally used in determining raw material availability policies in order to obtain minimum yields. This method will help plan raw material inventory in a company to be more efficient. In a manufacturing company, inventory is classified into three parts, specifically raw goods, semi-finished goods and finished goods. If a supply is sufficient then the production process will run smoothly. The purpose of this study is to make an analysis and make a control plan for milk raw materials contained in CV. Milkinesia Nusantara using the EOQ method. After analyzing the results obtained, the optimal purchase frequency is 240 times a year because milk raw materials are easily spoiled with a total purchase of milk raw materials every time one order is 119 liters, the main raw material is considered safe as much as 183 liters with what was ordered back when the raw material amounted to 457 liters. Then the total cost of availability of the company's raw materials, which was originally Rp. 85,023,395.55 - can be saved to Rp. 42,006,726, - so that the savings that occur are Rp. 43,016,669.55.